2013
DOI: 10.4141/cjas2012-017
|View full text |Cite
|
Sign up to set email alerts
|

Review: Anti-nutritional effects of phytic acid in diets for pigs and poultry – current knowledge and directions for future research

Abstract: Woyengo, T. A. and Nyachoti, C. M. 2013. Review: Anti-nutritional effects of phytic acid in diets for pigs and poultry Á current knowledge and directions for future research. Can. J. Anim. Sci. 93: 9Á21. Plant feedstuffs contain phytic acid (PA), which is a storage form of phosphorus. Phytic acid is, however, poorly hydrolyzed by pigs and poultry, and it has a capacity to complex dietary nutrients, thereby reducing nutrient digestibility. Reduced nutrient digestibility by PA implies reduced efficiency of utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(93 citation statements)
references
References 66 publications
1
88
1
3
Order By: Relevance
“…Several authors have reported an increment of Ca ATTD when the phytase enzyme has been added to the diet (Braña et al, 2006;Almeida et al, 2013) because Ca is chelated by phytic acid, regardless of its original form (Woyengo & Nyachoti, 2013). When phytase hydrolyses phytic acid, it releases the chelated Ca, making it available for the pigs to use.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported an increment of Ca ATTD when the phytase enzyme has been added to the diet (Braña et al, 2006;Almeida et al, 2013) because Ca is chelated by phytic acid, regardless of its original form (Woyengo & Nyachoti, 2013). When phytase hydrolyses phytic acid, it releases the chelated Ca, making it available for the pigs to use.…”
Section: Discussionmentioning
confidence: 99%
“…Assuena et al (2009) melaporkan bahwa fosfor memiliki peran penting dalam tubuh ayam, yaitu berperan dalam proses metabolisme dan secara khusus berperan penting dalam pertumbuhan ayam pedaging. Hal tersebut dikarenakan secara ekonomi, fosfor merupakan zat gizi yang memiliki nilai ekonomi tertinggi ketiga dalam formulasi ransum ayam pedaging setelah energi dan asam amino sehingga perlu dioptimalkan penggunaannya (Woyengo & Nyachoti 2013). Pemanfaatan asam fitat sebagai sumber fosfor dalam ransum ayam melalui proses hidrolisis pemecahan fosfat yang terikat fitat diharapkan dapat meningkatkan efisiensi penggunaan fosfor dalam ransum.…”
Section: Pendahuluanunclassified
“…Disamping kelebihan tersebut diatas, dedak padi memiliki kelemahan yang salah satunya adalah mengandung asam fitat yang dapat mengikat mineral sehingga penyerapan mineral akan terganggu. Kandungan asam fitat dalam diet untuk babi secara umum telah terbukti menurunkan penampilannya (Woyengo and Nyachoti, 2013). Kandungan fitat dalam pakan babi biasanya antara 7 dan 10 g / kg dari diet (Selle et al, 2009;National Research Council, 2012).…”
Section: Pengaruh Fitat Pada Monogastrikunclassified